Study about Management Control Procedures and Environment of Local Councils in Sierra Leone - Sualiho Sheriff; Micheal Tejan Gbenday (Research Developments in Arts and Social Studies Vol. 6, 2022)
The study assessed management control procedures and environment of Local Councils in Sierra Leone with reference to Bo and Kenema Districts Councils. The secondary objectives of the study were, to: 1) assess control procedures on the councils effectiveness; 2) assess control procedures in reducing fraudulent activities; 3) assess control procedures in promoting the councils performance; 4) identify the weaknesses in the control procedures; and 5) assess control procedures in achieving monitoring and supervision at the councils. The approach adopted for the study was a cross-sectional descriptive design, and the data were presented by the use of qualitative and quantitative methods. The target population of the study is twenty-eight (28) core staff members, out of which 26 core staff members were selected from both councils that adhered to control procedures and environment of Bo and Kenema Districts Councils. The approach adopted for the study was a cross-sectional descriptive design. Research design is the framework or blueprint for conducting meaningful research. The data were presented by the use of qualitative and quantitative methods. A four-point Likert scale was used, and questionnaires and documentary analysis were used as data collection tools. In order to improve performance and lessen control flaws, Bo District Council shows more support by adhering to its control processes. Control measures greatly benefited the councils at Kenema District Council in reducing its fraudulent activities, improving performance, and enhancing monitoring and supervision. The research paper therefore, recommends that the Local Service Commission should make available to the core staff members internal policies, acts and regulations to the 22 local councils in Sierra Leone. The study differs from earlier research by distinguished researchers in that it would assist organisations in reviewing, monitoring, and evaluating the councils’ control procedures by reducing fraudulent activities and management breaches. Additionally, it would benefit the Local Service Commission to improve its internal policies and practises to reduce the likelihood of false assertions that would hinder the councils’ operations.